HISTORICAL EVENTS OF SECOND WORLD WAR IN FRANCE IN HANNAH’S THE NIGHTINGALE NOVEL: HISTORICISM APPROACH - Hikmah, Andi; Ariani, Setya; Rahayu, Famala (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
The Second World War is a big event that happened in the past which involved almost all countries in the world and was recorded in the history of human life. The Nightingale is a novel set in the Second World War in France, written by Kristin Hannah. This research aims to find out and explain about historical events of the Second World War in France portrayed in The Nightingale novel using historicism. It is an approach that relates to the historical contexts themselves in understanding the history that exists in a literary work. In addition, this research also used a qualitative method was employed to fulfill the objectives of this research. The results showed that The Nightingale novel portrayed the historical events of the Second World War in France. Those descriptions of historical events were the Fall of France, Vichy in the persecution of the Jews, French resistance, and the liberation of France. In this case, the descriptions of these historical events were mostly portrayed in narration by Kristin Hannah.